Task Effects on Sentence Comprehension in Children with Autism Spectrum Disorder: Evidence from Sentence–Picture-Matching Tests - Maria Andreou; Konstantina Sonia Antoniou; Eleni Peristeri (Languages)
The present study compared two sentence–picture-matching tests in Greek, namely the Syntactic Proficiency Test and the sentence comprehension subtest of the Diagnostic Verbal Intelligence Quotient (DVIQ) battery, to assess complex sentence comprehension in 29 Greek-speaking children with autism spectrum disorder (ASD). Crucially, the DVIQ test included more foils and visual details than the Syntactic Proficiency Test. The study had three aims: (1) to examine sentence comprehension performance across various syntactically complex structures (passives, clitic pronouns, subject, and object relative clauses) and identify comprehension asymmetries among these types; (2) to investigate task effects on syntactic comprehension accuracy by comparing performance across the two tests; and (3) to examine differences in error types across tasks. Results showed that autistic children were significantly less accurate in their comprehension performance of passives and clitics in the DVIQ compared to the Syntactic Proficiency Test, with no difference in accuracy observed for subject or object relative clauses, which were consistently high and low, respectively, across both tests. Error patterns also differed across the two tests. More specifically, thematic role reversals in passives were more frequent in the DVIQ than the Syntactic Proficiency Test. The overall findings suggest that the DVIQ’s enhanced perceptual complexity may have affected children’s accuracy in their comprehension of passives and clitics, while object relatives were less affected by task effects because of their high structural complexity. The study highlights how visual complexity and foil count can impact syntactic comprehension in autistic children and underscores the importance of task design in assessing syntactic skills in ASD.